Perioperative factors that influence the outcome of microsurgical reconstructions in craniomaxillofacial surgery - Preidl, Raimund; Wehrhan, Falk; Schlittenbauer, T.; Neukam, Friedrich Wilhelm; Stockmann, Philipp (British Journal of Oral and Maxillofacial Surgery, 2015)
Microsurgical tissue transfer is a well-established way of reconstructing the head and neck, but there are still many postoperative complications that require revision. The aim of this study was to clarify perioperative factors and characteristics of patients that influence the success of the flap and the need for revision. We retrospectively studied 368 patients who were treated with microsurgical free tissue transfer in the head and neck area at the Department of Oral and Maxillofacial Surgery at the University Medical Centre, Erlangen, between 2004 and 2009. Investigations concentrated on patients' characteristics and operative factors. Free scapular or parascapular flaps (n=161, 44%) and radial forearm flaps (n=119, 32%) were predominantly used for the reconstruction of major defects in the mandible and the floor of the mouth. In 39 patients (11%) revision was required, which resulted in a success rate of 96%. There was a significant association between preoperative American Society of Anesthesiologists (ASA) grade and postoperative survival of the flap (p=0.04). Patients previously treated by irradiation required significantly more revisions than those not so treated (p=0.04). The use of vein grafts was also significantly associated with the need for revision (p=0.02). The ASA grade influenced the success rate but was not associated with the number of revisions. These factors must be taken into consideration when intervention is planned to reduce the number of postoperative complications and interventions further.
EVALuna2:24398